Embodying life-long learning: Transition and capstone experiences. (4th March 2017) - Butler, Des; Coe, Sandra; Field, Rachael; McNamara, Judith; Kift, Sally; Brown, Catherine
Abstract: This paper discusses the principle of Transition as it has been conceptualised by the Curriculum Renewal in Legal Education project. The project sought to develop a principled framework for renewing the final year of tertiary legal education in Australia. Capstone experiences were chosen as the most appropriate mechanism for assisting final year students to manage the transition process. Thoughtfully designed capstones assist students to integrate and synthesise their learning over their entire degree programme, facilitate closure on the undergraduate experience, and assist students to transition from student to emerging professional. We discuss the importance of addressing final year students' transitional needs and explain how the principle facilitates this process. Although the framework has been developed specifically for legal education in Australia its approach enables transferability across disciplines and institutions. The framework addresses criticisms that universities and law schools are not meeting the needs of final year students by preparing them for the transition to graduate life in a complex and uncertain world.